Prevalence of multiple antipsychotic use and associated adverse effects in Australians with mental illness. Issue 3 (September 2016) - Westaway, Kerrie; Sluggett, Janet K.; Alderman, Christopher; Procter, Nicholas; Roughead, Elizabeth
ABSTRACT: Aim: This article analyzes the prevalence of use of concurrent multiple antipsychotics and high dosage treatment in people with mental illness, to assess the burden of antipsychotic drug-related side-effects associated with multiple use, and to identify strategies shown to reduce antipsychotic polypharmacy. Methods: Literature reviewed was sourced from MEDLINE, Embase, CINAHL, InformIT, PsycINFO, International Pharmaceutical Abstracts, Cochrane Library database and Joanna Briggs Institute databases to identify Australian studies published between January 2000 and February 2015. Studies that reported prevalence of multiple antipsychotic use or addressed the issue of antipsychotic drug-related side-effects were included. Systematic reviews, randomized controlled trials, and observational pre–post studies of Australian and international interventions aiming to reduce multiple antipsychotic use in mental health settings were also identified. Results: Nineteen studies reporting prevalence of multiple antipsychotic use were identified. The proportion of patients taking more than one antipsychotic ranged from 5 to 61%. Of the studies assessing dosages used, between one-third and one-half of all patients taking multiple antipsychotics received doses higher than recommended. Data from one national study reported that people taking multiple antipsychotics were more likely to experience at least one side-effect in comparison to consumers taking a single antipsychotic (90 verses 80%). International evidence of direct trials of conversion from treatment regimens involving multiple antipsychotics to those based on monotherapy show that between 50 and 75% of people with serious mental illness could be successfully converted to single-agent treatment, with up to 25% obtaining an improvement in health and the remaining 50% staying well managed. Conclusion: Use of multiple antipsychotics is common among Australian people with mental illness, despite guidelines recommending that only one antipsychotic should be used in most cases. People taking more than one antipsychotic at a time are more likely to experience side-effects, and to receive higher than recommended antipsychotic doses. Direct trials that aimed to reduce multiple antipsychotic use suggest it is possible to effectively reduce therapy in the majority of people without worsening outcomes. Simple educational programmes targeting health professionals have not been found to be effective; however, complex multifaceted programmes and quality improvement programmes have demonstrated effect.